Initial Health Assessments and HIV Screening under the Affordable Care Act - Leibowitz, Arleen A. (PLoS One, 2015)
BACKGROUND: The Centers for Disease Control and Prevention (CDC) estimates that 156,300 (95% CI 144,100–165,900) Americans living with HIV in 2012 were unaware of their infection. To increase knowledge of HIV status, CDC guidelines seek to make HIV screening a routine part of medical care. This paper examines how routinely California primary care providers test for HIV and how providers’ knowledge of California’s streamlined testing requirements, use of sexual histories, and having an electronic medical record prompt for HIV testing, relate to test offers. METHODS: We surveyed all ten California health plans offered under health reform’s Insurance Exchange (response rate = 50%) and 322 primary care providers to those plans (response rate = 19%) to assess use of HIV screening and risk assessments. RESULTS: Only 31.7% of 60 responding providers reported offering HIV tests to all or most new enrollees and only 8.8% offered an HIV test of blood samples all or most of the time despite the California law requiring that providers offer HIV testing of blood samples in primary care settings. Twenty-eight of the 60 providers (46.6%) were unaware that California had reduced barriers to HIV screening by eliminating the requirement for written informed consent and pre-test counseling. HIV screening of new enrollees all or most of the time was reported by 53.1% of the well-informed providers, but only 7.1% of the less informed providers, a difference of 46 percentage points (95% CI: 21.0%—66.5%). Providers who routinely obtained sexual histories were 29 percentage points (95% CI: 0.2%—54.9%) more likely to screen for HIV all or most of the time than those who did not ask sexual histories. CONCLUSION: Changing HIV screening requirements is important, but not sufficient to make HIV testing a routine part of medical care. Provider education to increase knowledge about the changed HIV testing requirements could positively impact testing rates.